Comparison of Fecundity and Gall-Forming of the Horned-Gall Aphid, Schlechtendalia chinensis (Hemiptera: Aphididae) from Different Populations - Xin Xu; Zhaohui Shi; Chang Tong; Shuxia Shao; Hongyuan Wei; Zixiang Yang (Insects)
The horned-gall aphid, Schlechtendalia chinensis, is the most economically valuable Chinese gallnut aphid species, playing a decisive role in the production of Chinese gallnuts. The method of cultivating the gallnut species with artificial moss and increasing the yield of gallnuts after inoculation has been applied in the main producing areas of Chinese gallnuts. However, it is still unclear whether artificial cultivation affects the fecundity and gall-forming effect of S. chinensis. In this study, autumn migrant aphids of S. chinensis from wild, artificial and introduced populations were used as materials to cultivate and inoculate under the same environment. The number of male and female sexuales, fundatrices, the galls per tree, and the total weight of galls per tree in subsequent generations were analyzed, and differences in the fecundity and gall-forming effects of different populations were analyzed. The results showed that the fecundity of the wild population was stronger than that of the artificial population, and the number of aphids produced by a single spring migrant and the number of fundatrices increased by 75.86% and 81.62%, respectively. Compared with the introduced population, the survival rate of female sexuales in the local population was higher. Compared with the artificial population, the gall-forming effect of the wild population was better; the number of galls per tree, the weight of single gall, and the total weight of galls per tree increased by 68.33%, 50.77%, and 153.78%, respectively; and the gall preservation rate increased significantly. Artificial cultivation of S. chinensis will lead to a decrease in fecundity and gall-forming effect in subsequent generations, showing the degradation of the vitality of S. chinensis. Therefore, it is necessary to improve the effect of artificial cultivation of S. chinensis by adopting technical measures such as wild population or introduction.